Valuing virtue in medicine: a closer look at CanMEDS - Jayasinghe, Saroj (Canadian Medical Education Journal, 2024)
The CanMEDS-2015 Framework outlines seven key roles expected of practicing physicians: communicator, collaborator, manager, health advocate, scholar, and professional. Critics have expressed concern about the omission of a proposed eighth role, ‘Physician as Person’ relevant to humane qualities and personal resilience of the physician. Upon further analyses, the Framework has included several virtuous attributes in the roles of a physician as professional and communicator. However, it addresses certain virtues like creativity, love, and spirituality inadequately. Drawing on literature from Positive Psychology, the author categorizes and additional set of virtues into six classes: wisdom, courage, humanity, justice, temperance, and transcendence. Based on these, the author lists virtues and concepts relevant to a ‘Virtuous Role’ for physicians. The CanMEDS Framework should integrate these virtues as a foundational or overarching role and draw from Virtue Ethics in religious and philosophical traditions. This approach is timely, giving ongoing efforts to update and develop CanMEDS2025. By adopting a Virtuous Role within CanMEDS, we aim to train physicians who are technically skilled and deeply humane, meeting society's expectations for compassionate and virtuous healthcare professionals